(untitled) (Al-Mukhtar Journal of Economic Sciences, 2022)
The aim of the research is to identify the media role in agenda setting for audience and shaping public opinion towards democratic transformation and electoral participation. This research relied on the qualitative method and the second-level meta-analysis of the available published research. The researchers analyzed an available sample of research on the role of the media in democratic transition and electoral participation that the researchers were able to provide. They reach a number of results, including: The Libyan media played a role towards consolidating the manifestations of the democratic process in Libya by increasing the democratic awareness of the citizens and introducing them to the importance of spreading democracy. - Shedding light on human rights and the importance of preserving human rights and calling for the detection of any violation of these rights. - Calling for active and serious participation in the multiple elections that took place in Libya. - Activating the participation of women, whether in decision-making or in playing a positive political, social, economic and other role.- Introducing political parties and personalities and revealing the electoral programs for each of them. - Practicing criticism and oversight over governmental, legislative, judicial and other performance. - Standing against calls for separatism and racism. Informing the citizen of the latest developments in all aspects of Libyan life, politically, economically, socially, and militarily.